R for statistics - Cornillon, Pierre-Andre. (Boca Raton, FL : CRC Press, 2012)
'Foreword This book is the English adaptation of the second edition of the book'Statistiques avec R' which was published in 2008 and was a great success in the French-speaking world. In this version, a number of worked examples have been supplemented and new examples have been added. We hope that readers will enjoy using this book for reference when working with R. This book is aimed at statisticians in the widest sense, that is to say, all those working with datasets: science students, biologists, economists, etc. All statistical studies depend on vast quantities of information, and computerised tools are therefore becoming more and more essential. There are currently a wide variety of software packages which meet these requirements. Here we have opted for R, which has the triple advantage of being free, comprehensive, and its use is booming. However, no prior experience of the software is required. This work aims to be accessible and useful both for novices and experts alike. This book is organised into two main sections: the rst part focuses on the R software and the way it works, and the second on the implementation of traditional statistical methods with R. In order to render them as independent as possible, a brief chapter o ers extra help getting started (chapter 5, a Quick Start with R) and acts as a transition: it will help those readers who are more interested in statistics than in software to be operational more quickly'--
Includes bibliographical references and indexes.
Translated from the French.
Keywords: R (Computer program language); Mathematical statistics -- Data processing